Improving breakfast patterns of portuguese children - an evaluation of ready-to-eat cereals according to the European nutrient profile model - Rito, Ana (2019)
Background/objectives: Ready-to-eat cereal (RTEC) breakfasts have been increasing in Portugal, among children. Eat Mediterranean (EM), a Portuguese comprehensive community-based intervention, proposed to improve breakfast patterns of children and adolescents and to evaluate the healthiness of RTEC according to WHO/Europe nutrient profile model (Euro- NP). Subjects/methods: EM Program was developed during two scholar years (15/16 and 16/17) toward 2333 students (pre to secondary education). Data on breakfast was provided using a family record form. The intervention consisted of 257 educational sessions addressing the principles of Mediterranean Diet, and promoting a “healthy breakfast at home”. To check for compliance with Euro-NP, RTEC package food labels’ nutritional composition was used. Results: After intervention 92.9% of children/adolescents had breakfast daily with no report of breakfast skippers. RTECs were one of the most frequent (66.5%) breakfasts. Statistically significant improvements were showed for: daily qualitative and complete breakfast frequency (5.6%) and fruit (11.2%). Consumption of RTEC decreased 28%. According to Euro-NP, 84.6% of the RTECs were non-compliant, regarding sugar content. Children’s RTECs presented 5% more of energy and 26% more sugar than the “non-children’s” RTECs. Conclusion: EM strategy showed to be a successful program to improve patterns and quality of breakfast of the children and adolescents, reinforcing the importance of school-based nutritional programs in changing lifestyles. Nutrient profiling can be a useful tool to provide a selection of foods to be part of a healthy diet and can be used by policymakers to design policies to identify the foods to which marketing restrictions to children, will apply.